Exposure to anesthesia is not associated with development of α-synucleinopathies: A nested case-control study. (July 2021) - Laporta, Mariana L.; Kruthiventi, S. Chandralekha; Stang, Cole D.; Camerucci, Emanuele; Martin, David P.; Weingarten, Toby N.; Hanson, Andrew C.; Schroeder, Darrell R.; Warner, David O.; Savica, Rodolfo; Sprung, Juraj
Abstract: Introduction: Preclinical studies suggest that inhalational anesthetics may induce neuropathology changes in the nigrostriatal system, leading to development of α-synucleinopathies. We explored the role of general anesthesia in the development of Parkinson disease (PD) and other α-synucleinopathies. Methods: All α-synucleinopathy cases in Olmsted County, Minnesota, from January 1991, to December 2010, were identified from diagnostic codes, and then reviewed for type and index date of diagnosis. Cases were matched by sex and age (±1 year) to a referent control, a resident living in Olmsted County, and free of α-synucleinopathies before the index date (year of onset of the α-synucleinopathy). Medical records of both cases and controls were reviewed for lifetime exposure to anesthesia prior to the index date. Results: A total of 431 cases with clinically defined α-synucleinopathies were identified. Of these, 321 (74%) underwent 1, 069 procedures under anesthesia before the diagnosis date, and in the control group, 341 (79%) underwent 986 procedures. When assessed as a dichotomous variable, anesthetic exposure was not significantly associated with α-synucleinopathies (odds ratio [OR],  0.75; 95% CI, 0.54-1.05; P =.094). No association was observed when anesthetic exposure was quantified by the number of exposures (OR,  0.64,  0.89, and  0.74, for 1, 2–3, and ≥4 exposures, respectively, compared to no exposure as the reference; P =.137) or quantified by the cumulative duration of exposure assessed as a continuous variable (OR,  1.00; 95% CI, 0.97-1.02 per 1-h increase of anesthetic exposure; P =.776). Conclusions: We did not observe a significant association between exposure to general anesthesia and risk for the development of α-synucleinopathies. Highlights: Anesthetics may induce dopaminergic neurotoxicity at the nigrostriatal level. Preclinical studies suggest that anesthetics may induce α-synucleinopathies. α-synucleinopathies are not associated with exposure to anesthesia.